A control matching model predictive control approach to string stable vehicle platooning. (December 2015) - Kianfar, Roozbeh; Falcone, Paolo; Fredriksson, Jonas
Abstract: A predictive control strategy for vehicle platoons is presented in this paper, accommodating both string stability and constraints (e.g., physical and safety) satisfaction. In the proposed design procedure, the two objectives are achieved by matching a model predictive controller (MPC), enforcing constraints satisfaction, with a linear controller designed to guarantee string stability. The proposed approach neatly combines the straightforward design of a string stable controller in the frequency domain, where a considerable number of approaches have been proposed in literature, with the capability of an MPC-based controller enforcing state and input constraints. A controller obtained with the proposed design procedure is validated both in simulations and in the field test, showing how string stability and constraints satisfaction can be simultaneously achieved with a single controller. The operating region that the MPC controller is string stable is characterized by the interior of feasible set of the MPC controller. Abstract : Highlights: Obtaining string stability while fulfilling constraints resulted from safety, performance and limitations. Combine frequency domain control design technique together with MPC in control design. The proposed method is experimentally tested. Stability and feasibility are explicitly addressed.